Application of Cone Beam Computerized Tomography in Implantology (Journal of Orofacial Research, 2017)
Dental implants have gained immense popularity and wide acceptance because of its appearance and function simulating a natural tooth and its ability to replace the crown as well as the root of the missing tooth. It is important for dentists to be able to place the implants in the mandible and maxilla with a high degree of precision. The greater accuracy of Cone Beam Computed Tomography (CBCT) in measurements at lower radiation doses has made it a preferred option in implant dentistry. It has led to improvements in case selection and aids in both qualitative and quantitative measurement of bone, leading to a reduction in implant failure. This article provides an overview of the potential use of CBCT in implantology.